2019
DOI: 10.1108/tqm-12-2018-0193
|View full text |Cite
|
Sign up to set email alerts
|

Innovation through implementation of a quality improvement method

Abstract: Purpose The purpose of this paper is to analyse the effectiveness of a quality improvement method in driving innovation in the public sector. The study expands on the concept of innovation and analyses the types and usefulness of the innovations observed. Design/methodology/approach The study utilizes an action research approach. The aim of the quality improvement method introduced is to generate innovations enhancing efficiency. An interventionist research method is required to produce the findings. Data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…Although, literature shows the difference in QM practices in manufacturing and service industries because the manufacturing companies are in more advance level in the implementation of QM practices than service industries (Fotopoulos and Psomas, 2010; Sila and Ebrahimpour, 2005; Solis et al , 1998; Kaynak and Hartley, 2008). In recent times, few studies examine the impact of QM on innovation (Mättö, 2019; Sahoo, 2019; Salim et al , 2019; Zeng et al , 2015; Bon and Mustafa, 2013; Kim et al , 2012). The studies found great significance and positive association between innovation and QM and also have a greater impact on product quality.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Although, literature shows the difference in QM practices in manufacturing and service industries because the manufacturing companies are in more advance level in the implementation of QM practices than service industries (Fotopoulos and Psomas, 2010; Sila and Ebrahimpour, 2005; Solis et al , 1998; Kaynak and Hartley, 2008). In recent times, few studies examine the impact of QM on innovation (Mättö, 2019; Sahoo, 2019; Salim et al , 2019; Zeng et al , 2015; Bon and Mustafa, 2013; Kim et al , 2012). The studies found great significance and positive association between innovation and QM and also have a greater impact on product quality.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…When we look at the methodology methods from the emergence paradigm, it is surprising that complexity theory is seldom mentioned. Action research is conducted in only seven cases (Mättö, 2019; Malik et al , 2016; Gustavsson et al , 2016; Kassela et al , 2017; Mättö, 2019; Kennedy, 2020; Prashare, 2020; Unzueta et al , 2020). Avelar et al (2020) do not call it action research but do make use of direct involvement in the environment under study.…”
Section: Discussionmentioning
confidence: 99%
“…So much so that public service delivery has been described as one of the most significant features of public policy of the 1980s and 1990s (Barry, 1991 in Lapsley and Miller, 2019). However, despite such significance, although some studies try to explore the actual state of service delivery in the public sector (Bockel and Noordegraaf, 2006; Dimitriades and Maroudas, 2007; Karlsson et al , 2016; Mättö, 2019; Huque and Jongruck, 2020), very few of them focus on small island developing states (SIDSs) through the perception of public officers. In the quest of enhancing this most important legacy of NPM, this study, in the first instance, investigates the extent to which public officers of a small island state perceive that NPM is being practiced in their context.…”
Section: Introductionmentioning
confidence: 99%